2020
DOI: 10.1186/s13046-020-01673-0
|View full text |Cite
|
Sign up to set email alerts
|

CREB5 promotes invasiveness and metastasis in colorectal cancer by directly activating MET

Abstract: Background: cAMP responsive element binding protein 5 (CREB5) is a transcriptional activator in eukaryotic cells that can regulate gene expression. Previously, we found that CREB5 was involved in the occurrence and development of colorectal cancer (CRC) using bioinformatics analysis. However, the biological roles and underlying regulatory mechanism of CREB5 in CRC remain unclear. Methods: Real-time PCR, western blotting, and immunohistochemistry were used to examine CREB5 expression. In vitro experiments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 36 publications
(57 reference statements)
1
35
0
Order By: Relevance
“…Western blotting analysis was performed as previously described [ 44 ] using anti-SPON2 (A12077, ABclonal), anti-PYK2 (bs-3357R, Bioss), anti-p-PYK2 (bs-3400R, Bioss), anti-FAK (bs-1340R, Bioss), anti-Zyxin (60,254–1-Ig, Proteintech), anti-RhoA (HPA062346, Sigma-Aldrich), anti-cortactin (11,381–1-AP, Proteintech), anti-IL10 (20,850–1-AP, Proteintech), anti-CCL2 (66,272–1-Ig, Proteintech), and anti-CSF1 (14,779–1-AP, Proteintech) antibodies. Mouse monoclonal anti-α-tubulin antibody (RM2007, RayAntibody) was used as the internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting analysis was performed as previously described [ 44 ] using anti-SPON2 (A12077, ABclonal), anti-PYK2 (bs-3357R, Bioss), anti-p-PYK2 (bs-3400R, Bioss), anti-FAK (bs-1340R, Bioss), anti-Zyxin (60,254–1-Ig, Proteintech), anti-RhoA (HPA062346, Sigma-Aldrich), anti-cortactin (11,381–1-AP, Proteintech), anti-IL10 (20,850–1-AP, Proteintech), anti-CCL2 (66,272–1-Ig, Proteintech), and anti-CSF1 (14,779–1-AP, Proteintech) antibodies. Mouse monoclonal anti-α-tubulin antibody (RM2007, RayAntibody) was used as the internal control.…”
Section: Methodsmentioning
confidence: 99%
“…(40) MET is a transmembrane tyrosine kinase that are frequently reported in various types of cancers including in NSCLC and colorectal cancer. (41,42) Study in lung cancer cell line has shown that the MET was involved in the regulation of cell migration and invasion. (17) On the other hand, ACVR1, or Activin receptor 1, has been identified as one of the target gene that regulate metastasis, angiogenesis and lymph angiogenesis in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) staining and scoring were performed as previously described ( 21 ) using anti-FOXS1 (Sigma, HPA042475), anti-CD31 (Abcam, Cambridge, MA, USA, ab9498), and anti-CXCL8 (Bioss, bs-0780R) antibodies. The degree of IHC staining was reviewed and scored independently by two observers.…”
Section: Methodsmentioning
confidence: 99%